E-administration digital services in Poland - Kasprzyk, Beata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Common digitization of the e-services sector currently represents the basis for social and economic development. The development of e-administration is one of the key components of the process of building an information society. The paper presents the level of using e-services of public administration in Poland and EU-28 countries. The analysis covers empirical data of the GUS and Eurostat from the years 2008–2015. The scale of using the electronic citizen – office contact channel is very diverse in Europe. The term ”information society” understood as the universal character of using both the Internet and e-services of administration refers to such countries as: Denmark, Estonia, Norway, Finland and the Netherlands where the percentage of people using e-services in 2015 amounted to 88%–75%. Polish citizens in rankings in this area of activity turn out to be definitely weak, placed at the last positions. The paper attempted to point out some objective factors that explain this state of affairs. It turned out that the low level of use is determined and depends on the age of Internet users, level of education, place of residence or income earned in the household. The most advanced in electronic administration services is the population of young people (aged 25-44) and people with a higher level of education. Also high income and inhabitancy in large cities represent determinants of a higher percentage of those using the Internet and e-administration services. Those digitally excluded from this area, one is trying to activate through digital programs implemented since 2001, including the latest ”Integrated State IT Implementation Program” adopted in 2016.

Powszechna cyfryzacja sektora e-usług stanowi współcześnie podstawę rozwoju społecznego i gospodarczego. Rozwój e-administracji stanowi jeden z kluczowych czynników procesu budowy społeczeństwa informacyjnego. W artykule został przedstawiony poziom korzystania z e-usług administracji publicznej w Polsce i krajach UE-28. Analizie podlegały dane empiryczne GUS i Eurostat z lat 2008–2015. Skala korzystania z elektronicznego kanału kontaktów obywatel – urząd jest w Europie mocno zróżnicowana. Termin „społeczeństwo informacyjne” rozumiane jako powszechność korzystania zarówno z Internetu, jak i z e-usług administracji dotyczy takich krajów jak: Dania, Estonia, Norwegia, Finlandia i Holandia, gdzie odsetek osób korzystających z e-usług w 2015 r. wynosił 88% – 75%. Obywatele polscy w rankingach z tego obszaru aktywności wypadają zdecydowanie słabo, znajdując się na ostatnich lokatach. W artykule próbowano wskazać na pewne czynniki natury obiektywnej, wyjaśniającej taki stan rzeczy. Okazało się, że niski poziom korzystania jest zdeterminowany i zależny od wieku użytkowników Internetu, poziomu wykształcenia, miejsca zamieszkania czy dochodów osiąganych w gospodarstwie domowym. Najbardziej zaawansowana w usługi elektroniczne z administracją jest populacja ludzi młodych (w wieku 25–44 lata) oraz osób z wyższym poziomem wykształcenia. Także wysokie dochody i zamieszkiwanie w dużych miastach stanowią wyznaczniki wyższego odsetka zarówno korzystających z Internetu, jak i z usług e-administracji. Wykluczonych cyfrowo z tego obszaru próbuje się zaktywizować poprzez programy cyfrowe realizowane od 2001 roku, w tym przyjęty najnowszy w 2016 roku „Program Zintegrowanej Informatyzacji Państwa”.
Keywords: Information society; Internet services; Information and Communication Technology; Digital Divide; e-government; społeczeństwo informacyjne; e-administracja; e-wykluczenie